Tetrazine bioorthogonal chemistry derived in vivo imaging - Zhao, Gaoxiang; Li, Zhutie; Zhang, Renshuai; Zhou, Liman; Zhao, Haibo; Jiang, Hongfei (Frontiers in Molecular Biosciences, 2022)
Bioorthogonal chemistry represents a series of high-yielding biocompatible reactions that proceed selectively and rapidly in biological environments without side reactions towards various endogenous functional groups. Rooted in the principles of physical reactions, bioorthogonal reactions are intrinsically selective transformations not commonly found in biological environments. Bioorthogonal chemistry have long been applied to tracking and real-time imaging of biomolecules in their physiological environments. Thereinto, tetrazine bioorthogonal reactions are particularly important and have increasing applications in those fields owing to their unique properties of easily controlled fluorescence or radiation off-on mechanism, which greatly facilitate the tracking of real signals without been disturbed by background. In this mini review, tetrazine bioorthogonal chemistry (TBC) for in vivo imaging applications will be attentively appraised to raise some guidelines for prior tetrazine bioorthogonal chemical studies